The Language of Trauma Narrative Communication Management: Perspectives from a Corpus-based Approach - Chin, Shy Wei (Journal of Techno-Social, 2022)
Trauma experiences or post-traumatic disorders prove to be an uprising phenomenon faced by people around the globe. This paper examines the language of trauma studies in two textbooks authored by a prominent trauma analysis expert who has been in the field for more than 20 years. This paper posits that the study or content analysis of trauma narratives discourse textbooks could contribute to self-efficacy beliefs especially in communication management. Using the corpus-based approach, essential keywords, and a word list of the essential language of trauma headwords are identified. Thus, with the 209 identified headwords, the development of the new word list specifically to trauma narratives discourse has been facilitated. The production of the word list of the language of trauma is aimed to assist disaster risk management researchers and authorities in identifying the ‘sensitive’ traumatic keywords to be or not to be narrated to the affected people in community-based studies. Thus, this study entails insightful concepts to the creation of a trauma narrative essential word because of its meaningful application. In conclusion, the article presents the keywords found to be associated closely with trauma narrative textbooks insights and proposes a coping alternative to the community or academia from a linguistics and communication management point of view.